Evaluación Externa de la Universidad Nacional de Córdoba - Cangiano, Miguel; Catalán, César; Ciuro Caldini, Miguel Ángel; Del Bello, Juan Carlos; Fliess, Enrique; Garces, Luis; Ginestar, Ángel; Guerín, Miguel; Guaglianone, Ariadna; Lohe, Rodolfo; López Dávalos, Arturo; Pérez Lindo, Augusto; et al. (Universidad Nacional de Córdoba, 2019)
Fil: Cangiano, Miguel. Universidad Nacional de Córdoba; Argentina.